Rozwiąż równania ze wzorów:
1)(a+b)²=a²+2ab+b²
2)(a-b)²=(a-b)*(a-b)
3)(a*b)*(a+b)=a²b²

a) (x+6)²=(x-2)²
b) 4x(x-2)=(2x+4)²
c) x(2x-1)=2(x+2)²
d) 2x-x²=1-(x+3)²
e) (x+1)²+(x-2)²=2(x-1)(x+1)
f)(3x-4)²+4(2x+1)²=(5x+2)(5x-2)

Proszę o szybką odp;)

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-09T19:08:49+01:00
A) (x+6)²=(x-2)²
x²+12x+36=x²-4x+4
8x=-32
x=-4

b)4x(x-2)=(2x+4)²
4x²-8x=4x²+16x+16
-32x=16 / (-32)
x=-½

c) x(2x-1)=2(x+2)²
2x²-x=2(x²+4x+4)
2x²-x=2x²+8x+8
-9x=8 / (-9)
x=-8/9


d) 2x-x²=1-(x+3)²
2x-x²=1-(x²+6x+9)
2x-x²=1-x²-6x-9
2x-x²+x²+6x=-8
8x=8
x=1

e) (x+1)²+(x-2)²=2(x-1)(x+1)
x²+2x+1+x²-4x+4=2(x²-1)
2x²-2x+5=2x²-2
-2x=-7/(-2)
x=3,5


f)(3x-4)²+4(2x+1)²=(5x+2)(5x-2)
9x²-24x+16 +4(4x²+4x+1)=25x²-4
9x²-24x+16 +16x²+16x+4=25x²-4
-8x=-16/(-8)
x=2